SISTEM PAKAR DIAGNOSA PENYAKIT TANAMAN PADI BERBASIS WEB - Setyowati, Dwi; Permana, Yudha Indra (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2013)
Expert system for analysis of disease in rice is a computer-based system for analysis and diagnosis of diseases in rice based on the symptoms that are displayed on the search process. System design goal is to help farmers to know the type of disease in rice plants as well as instructions given solution and the solution given by an expert.Design of an expert system was built using the method of forward chaining in which the searches performed with the technique in detail and the detail so that the search process is obtained as solutions of the selected problems.Advantages of this method is the description of the algorithm and a knowledge base that is comparable to the analysis of the problem, so the results given the results obtained in the order and detail. Expert system for analysis of disease in rice plants created uses programming language Delphi 7.0 with MySQL. By using an expert system is expected to acquire the system user the ease in obtaining the information needed regarding the analysis and diagnosis of disease in rice.